Evaluation of exfoliative cytology in the diagnosis of oral premalignant and malignant lesions: A cytomorphometric analysis - Renuka Verma; Anil Singh; Manjunath Badni; Akhilesh Chandra; Shalini Gupta; Ruchita Verma (Wolters Kluwer Medknow Publications, 2015)
Background: Many oral squamous cell carcinomas (OSCCs) arise within regions that previously had premalignant lesion. Early diagnosis and prompt treatment of premalignant lesions offers the best hope of improving the prognosis in patients with OSCC. Exfoliative cytology is a simple and non-invasive diagnostic technique that could be used for early detection of oral premalignant and malignant lesions. This study was undertaken to evaluate the quantitative changes in nuclear area (NA), cytoplasmic area (CA) and nuclear-to-cytoplasmic ratio (NA/CA) in cytological buccal smears of oral leukoplakia with dysplasia (OLD) and OSCC patients while comparing with normal healthy mucosa. Materials and Methods: A quantitative study was conducted over 90 subjects including 30 cases each of OLD, OSCC and clinically normal oral mucosa. The smears obtained were stained with Papanicolaou (PAP) stain and cytomorphological assessment of the keratinocytes was carried out. The statistical tools included arithmetic mean, standard deviation, Chi-square test, analysis of variance, Tukey multiple comparison. P < 0.001 was considered as significant. Results: The mean NA of keratinocytes in the normal mucosa was 65.47 ± 4.77 μm 2 while for OLD it was 107.97 ± 5.44 μm 2 and 139.02 ± 8.10 μm 2 for that of OSCC. The differences show a statistically significant increment in NA (P < 0.001). There was significant reduction (P < 0.001) in the CA of keratinocytes from OSCC when compared with those from smears of OLD and normal mucosa with the values of 1535.80 ± 79.38 μm 2 , 1078.51 ± 56.65 μm 2 and 769.70 ± 38.77 μm 2 respectively. The NA/CA ratio in the smears from normal oral mucosa, OLD and OSCC showed a mean value of 0.043 ± 0.004, 0.100 ± 0.008, 0.181 ± 0.015 respectively with a significant difference among the groups (P < 0.001). Conclusion: Evaluation of nuclear and CA of keratinocytes by cytomorphometry can serve as a useful adjunct in the diagnosis and prognosis of a dysplastic lesion which may lead to OSCC.